A Cross-Lagged Panel Approach to Understanding Social Support and Chronic Posttraumatic Stress Disorder Symptoms in Veterans: Assessment Modality Matters. Issue 5 (September 2018) - Woodward, Matthew J.; Morissette, Sandra B.; Kimbrel, Nathan A.; Meyer, Eric C.; DeBeer, Bryann B.; Gulliver, Suzy B.; Gayle Beck, J.
Abstract: Although there is a strong and consistent association between social support and posttraumatic stress disorder (PTSD), the directionality of this association has been debated, with some research indicating that social support protects against PTSD symptoms, whereas other research suggests that PTSD symptoms erode social support. The majority of studies in the literature have been cross-sectional, rendering directionality impossible to determine. Cross-lagged panel models overcome many previous limitations; however, findings from the few studies employing these designs have been mixed, possibly due to methodological differences including self-report versus clinician-administered assessment. The current study used a cross-lagged panel structural equation model to explore the relationship between social support and chronic PTSD symptoms over a 1-year period in a sample of 264 Iraq and Afghanistan veterans assessed several years after trauma exposure. Approximately a third of the sample met criteria for PTSD at the baseline assessment, with veterans' trauma occurring an average of 6 years prior to baseline. Two separate models were run, with one using PTSD symptoms assessed via self-report and the other using clinician-assessed PTSD symptoms. Excellent model fit was found for both models. Results indicated that the relationship between social support and PTSD symptoms was affected by assessment modality. Whereas the self-report model indicated a bidirectional relationship between social support and PTSD symptoms over time, the clinician-assessed model indicated only that baseline PTSD symptoms predicted social support 1 year later. Results highlight that assessment modality is one factor that likely impacts disparate findings across previous studies. Theoretical and clinical implications of these findings are discussed, with suggestions for the growing body of literature utilizing these designs to dismantle this complex association. Highlights: A sample of 264 veterans were assessed an average of 6 years after trauma exposure Results showed that clinician assessed PTSD predicted social support 1 year later A self-report model of PTSD found bidirectional paths between these variables Findings indicate that assessment modality influenced findings Results suggest more longitudinal multi-method studies of this dynamic are needed